Implementasi Aplikasi Psikotes Berbasis Android pada Lembaga Psikologi Terapan Widya Prasethya - Andri Sugyanto; Amhar Davi Dewantara; Rivani Rustam Pabe (KOLONI, 2022)
Psychological tests are assessments designed to measure various psychological aspects of an individual. These tests can take the form of written, projective, or verbal evaluations. In this research, the development of a psychological test model is centered around Android-based technology due to its robust security efficiency. This is substantiated by the growing number of internet transactions conducted via Android smartphones. Android-based psychological testing is a system developed to enhance an individual's psychological testing capabilities using an Android smartphone. The primary objective of this research is to serve as a platform for training individuals in psychological testing skills, enabling them to readily undergo various psychological assessments when applying for jobs, all facilitated through the use of an Android smartphone. This approach is expected to provide an alternative means of simplifying and streamlining the psychological testing process, making it more efficient. The system was created using the Eclipse Indigo application as a Java programming language editor, and database management was accomplished using MySQL. Keywords: Psychological tests, Eclipce Indigo, Java, MySQL